LANGUAGE ANALYSIS TOWARD NEWS OF FOOTBALL AND SUPPORTER CONFLICT IN SOCIOLOGICAL REVIEW - Carla Maretha; Yulia Wahyuningsih; Gali Alrajafi (SIGEH ELT : Journal of Literature and Linguistics, 2022)
In this paper, the approach used is a sociological approach. The sociological approach is described by the plurality that is present in Indonesia within the framework of Bhineka Tunggal Ika and Pancasila as the nation's ideology. this paper uses qualitative research. In connection with the formulation of the question in this paper, what are the common causes of conflict between supporters of soccer teams in Indonesia, and after analyzing, explaining, and describing the facts obtained, the author can conclude that the theory of conflict or conflict with its three dimensions is effective for recognizing the behavior of conflicting individuals or groups. In this case, it is the supporters of the Indonesian teams. Then it can also be concluded that the proposed hypothesis can be justified, namely prestige, fanaticism, and revenge are common causes of conflict between groups supporting eleven teams in Indonesia.